Seasonal incidence of mango stem borer, Batocera rufomaculata (Coleoptera: Cerambycidae) in north-western Himalayan region of India - SINGH, CHANDER; RANA, VIRENDER KUMAR; CHANDEL, VISHAV GAURAV SINGH; SAHIL, KARTIKEY (The Indian Journal of Agricultural Sciences, 2026)
The mango stem borer, Batocera rufomaculata De Geer (Coleoptera: Cerambycidae) is a serious pest of concern affecting mango (Mangifera indica L.) orchards, causing substantial damage to fruit trees. This study was carried out from June 2020–May 2021 at Regional Horticultural and Forestry Research Station, Bhota, Hamirpur, Himachal Pradesh to evaluate the seasonal incidence patterns of B. rufomaculata in relation to key abiotic factors such as temperature, rainfall and relative humidity. Infestation was identified based on visible signs such as fresh frass, oozing gum and larval tunnels which revealed that B. rufomaculata was active from June to October with peak incidence in July (43.75%). Statistical analysis revealed a significant positive correlation between pest incidence and both maximum temperature (r = 0.90) and minimum temperature (r = 0.96), highlighting strong influence of temperature on infestation. Rainfall (r = 0.71) and relative humidity (r = 0.70) also contributed positively, though to a lesser extent. A multiple regression model incorporating these variables explained 96.95% of the variance in infestation levels (R2 = 0.96), confirming the strong predictive power of these abiotic factors. These findings highlight the strong influence of monsoon-associated temperature and moisture on borer activity and provide baseline information useful for forecasting and timely implementation of management strategies against B. rufomaculata in mango orchards of the north-western Himalayas, particularly in the era of shifting climatic conditions.